Disrupted brain network topology in pediatric posttraumatic stress disorder: A resting-state fMRI study - Suo, Xueling; Lei, Du; Li, Kaiming; Chen, Fuqin; Li, Fei; Li, Lei; Huang, Xiaoqi; Lui, Su; Li, Lingjiang; Kemp, Graham J.; Gong, Qiyong (Human brain mapping, 2015)
Children exposed to natural disasters are vulnerable to the development of posttraumatic stress disorder (PTSD). Recent studies of other neuropsychiatric disorders have used graph‐based theoretical analysis to investigate the topological properties of the functional brain connectome. However, little is known about this connectome in pediatric PTSD. Twenty‐eight pediatric PTSD patients and 26 trauma‐exposed non‐PTSD patients were recruited from 4,200 screened subjects after the 2008 Sichuan earthquake to undergo a resting‐state functional magnetic resonance imaging scan. Functional connectivity between 90 brain regions from the automated anatomical labeling atlas was established using partial correlation coefficients, and the whole‐brain functional connectome was constructed by applying a threshold to the resultant 90 * 90 partial correlation matrix. Graph theory analysis was then used to examine the group‐specific topological properties of the two functional connectomes. Both the PTSD and non‐PTSD control groups exhibited “small‐world” brain network topology. However, the functional connectome of the PTSD group showed a significant increase in the clustering coefficient and a normalized characteristic path length and local efficiency, suggesting a shift toward regular networks. Furthermore, the PTSD connectomes showed both enhanced nodal centralities, mainly in the default mode‐ and salience‐related regions, and reduced nodal centralities, mainly in the central‐executive network regions. The clustering coefficient and nodal efficiency of the left superior frontal gyrus were positively correlated with the Clinician‐Administered PTSD Scale. These disrupted topological properties of the functional connectome help to clarify the pathogenesis of pediatric PTSD and could be potential biomarkers of brain abnormalities. Hum Brain Mapp 36:3677–3686, 2015. © 2015 Wiley Periodicals, Inc.